2013
DOI: 10.1371/journal.pone.0067442
|View full text |Cite
|
Sign up to set email alerts
|

Study on Citrus Response to Huanglongbing Highlights a Down-Regulation of Defense-Related Proteins in Lemon Plants Upon ‘Ca. Liberibacter asiaticus’ Infection

Abstract: Citrus huanglongbing (HLB) is a highly destructive disease of citrus presumably caused by ‘ Candidatus Liberibacter asiaticus ’ (Las), a gram-negative, insect-transmitted, phloem-limited α-proteobacterium. Although almost all citrus plants are susceptible to HLB, reports have shown reduced susceptibility to Las infection in lemon ( Citrus limon ) plants. The aim of this study is to identify intra-species specific molecular mechanisms associated with Las-induced responses in lemon plants. To achieve this, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 52 publications
5
74
0
3
Order By: Relevance
“…Liberibacter asiaticus" lacks type II plant cell wall-degrading enzymes (54), which have been known to play important roles in plant signaling to induce defense responses against fungal pathogens through autodegradation products of the plant cell wall (cell wall fragments or oligogalacturonides) (53). Moreover, studies have shown that the plant defense system is suppressed by HLB disease (42,52,55,56). This weakened defense system in HLB-affected citrus trees could explain their increased susceptibility to other pathogens such as diplodia.…”
Section: Discussionmentioning
confidence: 99%
“…Liberibacter asiaticus" lacks type II plant cell wall-degrading enzymes (54), which have been known to play important roles in plant signaling to induce defense responses against fungal pathogens through autodegradation products of the plant cell wall (cell wall fragments or oligogalacturonides) (53). Moreover, studies have shown that the plant defense system is suppressed by HLB disease (42,52,55,56). This weakened defense system in HLB-affected citrus trees could explain their increased susceptibility to other pathogens such as diplodia.…”
Section: Discussionmentioning
confidence: 99%
“…The 56 down-regulated proteins were associated with protein synthesis, protein folding and photosynthesis. On the contrary, the defense-related proteins were down-regulated in lemon that is tolerant to HLB, such as lectin-related proteins, chitinase, and miraculin-like proteins [37]. Upon HLB infection, chaperones HSP 70 and an isoflavone reductase-related protein were up-regulated in lemon.…”
Section: Can Crispr Win the Battle Against Huanglongbing?mentioning
confidence: 95%
“…Upon HLB infection, chaperones HSP 70 and an isoflavone reductase-related protein were up-regulated in lemon. Proteins associated with photosynthesis and starch synthesis were similar to grapefruit and sweet orange [37]. The differences in responses between HLB susceptible and tolerant cultivars were determined by proteomes between Navel orange (susceptible) and Volkameriana (moderately tolerant) [38].…”
Section: Can Crispr Win the Battle Against Huanglongbing?mentioning
confidence: 99%
“…This can cause a sharp reduction of the photosyntates production in those leaves as pointed by (Nwugo et al, 2013;Xu et al, 2015). In some cases there is also a premature leaf drop (Robles-González et al, 2010).…”
Section: Number Of Fruits Per Square Meter Of Treetopmentioning
confidence: 99%
“…Esto puede provocar una fuerte reducción en la producción de fotosintatos en esas hojas como lo señalan (Nwugo et al, 2013;Xu et al, 2015). En algunos casos se presenta además la caída prematura de hojas (Robles-González et al, 2010).…”
Section: Cuadro 1 Número De Frutos Por Munclassified